2019
DOI: 10.21603/2078-8975-2019-21-2-395-402
|View full text |Cite
|
Sign up to set email alerts
|

Method of Synchronized Fractal and Musical Dynamics as a Means to Achieve Altered States of Consciousness

Abstract: This paper continues the cycle of interdisciplinary studies that feature a new technology of audiovisual induction of altered states of consciousness. The technology is based on a combination of models, methods, and approaches of psychology, mathematics, and computer science. The research objective was to prove that the technology can induce relaxation states. The authors conducted two experiments with a specific configuration of synchronized fractal and musical sequences. The study involved 47 people, who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…To test the hypothesis, we selected a special configuration of the dynamic fractals method. The main colors of the fractal palette are blue and beige, as the colors had a positive effect on the well-being and relaxation of the subjects in the last experiment [7]. The composition of John Baker -Rocket Rap was chosen as the musical accompaniment (rendering a fractal for this composition leads to the correct visual row).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the hypothesis, we selected a special configuration of the dynamic fractals method. The main colors of the fractal palette are blue and beige, as the colors had a positive effect on the well-being and relaxation of the subjects in the last experiment [7]. The composition of John Baker -Rocket Rap was chosen as the musical accompaniment (rendering a fractal for this composition leads to the correct visual row).…”
Section: Methodsmentioning
confidence: 99%
“…This method has shown its effectiveness for the induction of altered states of consciousness (ASC), including the creative states of consciousness (CSC); it can increase personal and group creativity and leads to changes in the degree of manifestation of new value-semantic concepts (before and after exposure) [6]. In addition, we have shown that the developed method leads to a relaxing effect [7]. Theoretical studies also clearly demonstrate that all of the above parameters are important for the development and realization of the potential of a creative leader.…”
Section: Introductionmentioning
confidence: 99%